Sustainable economic development challenges faced by managers of small, medium and micro enterprises (SMMEs) at Lepelle Nkumpi Municipality in the Limpopo Province - Mashilo, Kakaru Sinah (My University, 2022)
Unemployment in South Africa has prompted the government to shift focus in terms of employment creation resulting in encouraging citizens to become entrepreneurs. This took effect after 1994 and small, medium, and micro enterprises (SMMEs) have since been the important drivers of the economy. They have provided jobs to many unemployed people and reduced poverty in many communities. Despite their importance, these enterprises encounter challenges that threaten their sustainability and growth. The purpose of the study was to investigate the internal and external factors affecting SMMEs. To get a clear understanding of the challenges confronting managers of SMMEs in Lepelle Nkumpi Municipality (LNM), a comprehensive investigation of this problem was conducted through a literature review. The study adopted a mixed method approach, where the researcher used both qualitative and quantitative methods to elicit information from the participants. The study also adopted the interpretivism and positivism paradigms. Data were collected through the usage of structured questionnaires and semi-structured interviews from the respondents who were selected purposively. Analysis of quantitative data was done through SPSS and presented in tables, graphs, and pie charts. For qualitative data, thematic analysis was used. The findings confirmed what was reviewed in the literature, namely, that managers of SMMEs encounter operational difficulties; and inaccessibility of funding is a major challenge. The study revealed that 78% of the respondents used personal savings and some borrowed from friends and family, whilst only 22% received funding as a form of government grants and bank loans. To confront the challenges of funding, government and parastatals should ensure that SMMEs receive funding in an impartial manner; and government should also serve as collateral for SMMEs with financial institutions in cases where government could not offer funding since lack of collateral proved to be a blockade for SMMEs. Chapter 5 of this research report provides a conclusion and recommendations arising from the data collection on the improvement and accelerated support to ensure the sustainability and growth of SMMEs.
Thesis (M.Dev. (Planning and Management)) -- University of Limpopo, 2022
Keywords: Unemployment; Sustainable; Economic Development; Small, Medium and Micro Enterprises (SMMEs); Economic development; Economic development -- South Africa -- Limpopo; Small business -- South Africa -- Limpopo; Sustainable development -- South Africa -- Limpopo